SRE for Healthcare: MTTR Optimization in Cigna’s Claims Systems - Sai Raghavendra Varanasi (International Journal of Computational and Experimental Science and Engineering, 2025)
In the healthcare industry, time is more than money it can be the difference between accurate care delivery and administrative chaos. As systems scale to serve millions of claims daily, the reliability of infrastructure that underpins insurance processing becomes mission-critical. This paper focuses on how Site Reliability Engineering (SRE) principles were applied to optimize Mean Time to Recovery (MTTR) in Cigna’s claims processing systems. We walk through a robust strategy combining observability, incident automation, chaos engineering, and smart escalation policies that led to significant reductions in service downtime and faster recovery from production incidents improving both operational efficiency and regulatory compliance in a heavily governed domain.